2012
DOI: 10.5005/jp-journals-10021-1075
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Accuracy of 0.022 Slots at Face, Base and Mesial and Distal Surface of Brackets marketed by Different Manufacturers

Abstract: The aim of the present study was to compare the accuracy of the bracket slot dimension at base and at face and at the mesial and distal surfaces of conventional 0.022 slot metal brackets marketed by different manufacturers. Materials and methods:Twenty brackets each of 0.022 inch upper left central incisor brackets from five different manufacturers were taken for evaluation of slot dimensions with a stereomicroscope. The images obtained were calibrated with a software (Dewinter Biowizard 4.3). The bracket slot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
4
3
0
Order By: Relevance
“…The results of the present study showed that the mean slot width at base was minimum for Master Brackets (American Ortho) (0.021130 ± 0.00017) inch and maximum for Mini Diagonali (Leone) (0.022170 ± 0.00011) inch. The mean values of slot base width for Equilibrium (Dentaurum) and Leone group of the present study were 0.022110 inch and 0.022110 inch respectively and these values were similar to a study done by Karan Tangri et al 14 as the values were 0.0222 inch and 0.022 inch respectively. In their study the mean value of slot base width of Sapphire (Modern Ortho) was 0.0209 inch whereas this measurement was 0.021850 inch in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the present study showed that the mean slot width at base was minimum for Master Brackets (American Ortho) (0.021130 ± 0.00017) inch and maximum for Mini Diagonali (Leone) (0.022170 ± 0.00011) inch. The mean values of slot base width for Equilibrium (Dentaurum) and Leone group of the present study were 0.022110 inch and 0.022110 inch respectively and these values were similar to a study done by Karan Tangri et al 14 as the values were 0.0222 inch and 0.022 inch respectively. In their study the mean value of slot base width of Sapphire (Modern Ortho) was 0.0209 inch whereas this measurement was 0.021850 inch in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study various bracket systems were compared and statistically significant differences (p<0.001) were found in the slot dimensions of various manufacturers. This finding was in agreement with the studies done by Karan et al 14 , Youngran et al 17 and Laura et al 18 .…”
Section:  Slot Width At Top Of Various Bracket Systemssupporting
confidence: 94%
See 1 more Smart Citation
“…Tangri et al analyzed twenty 0.022 × 0.028‐in. brackets from five different manufacturers, using a stereomicroscope (Tangri & Kumar, ). A significant difference of the slot size was observed for all of the brackets, both at base and at face.…”
Section: Discussionmentioning
confidence: 99%
“…Use of undersized archwires may directly and adversely affect the three dimensional tooth positioning. 1 Achieving a satisfactory inclination or torque of the incisors is important for the final esthetic result. Torque expression depends upon a number of factors including the size of the bracket slots and archwires.…”
Section: Introductionmentioning
confidence: 99%